Presentation for the Special Issue “Sociolinguistics and the Teaching of Foreign Languages” of Revista Entrelínguas - Sandes, Egisvanda Isys de Almeida; Manjón-Cabeza Cruz, Antonio; Molina Ortés, Elena Fernández de (Universidade Estadual Paulista, 2020)
This is an introduction to the proposed theme, in which the importance of sociolinguistic studies for the teaching, acquisition and learning of languages is emphasized. In addition, each text of the material is presented, starting with interviews with significant and current representatives of the variation sociolinguistics (Francisco Moreno Fernández and Juan Manuel Hernández Campoy) from the Hispanic and Anglo-Saxon spheres, respectively; then, it discusses the ten articles that deal with the theme from two perspectives: linguistic attitudes and beliefs of speakers and linguistic norms and policies. Finally, the reviews of two books related to the Special issue are commented: The Routledge handbook of Spanish as a heritage language, edited by Kim Potowsky, 2018, New York, Routledge publisher, and La trastienda de la enseñanza de lenguas extranjeras, by Francisco García Marcos, 2018, from the Interlingua collection of Editora Comares de Granada / Spain. The presentation is an invitation to readers to enjoy reading the Special issue.